Determinants of Resting Oxidative Stress in Middle-Aged and Elderly Men and Women: WASEDA'S Health Study. (8th June 2021) - Kawamura, Takuji; Tanisawa, Kumpei; Kawakami, Ryoko; Usui, Chiyoko; Ito, Tomoko; Tabata, Hiroki; Nakamura, Nobuhiro; Kurosawa, Sayaka; Choi, Wonjun; Ma, Sihui; Radak, Zsolt; Sawada, Susumu S.; et al.
Abstract : Previous studies have not investigated the determinants of resting oxidative stress, including physical fitness, as it relates to redox regulation. The present study therefore was aimed at identifying lifestyle and biological factors that determine resting oxidative stress, including objectively measured physical fitness. In 873 middle-aged and elderly men and women, age and anthropometric parameters, lifestyle-related parameters, medication and supplementation status, physical fitness, biochemical parameters, and nutritional intake status, as well as three plasma oxidative stress markers: protein carbonyl (PC), F2 -isoprostane (F2 -IsoP), and thiobarbituric acid reactive substances (TBARS), were surveyed and measured. The determinants of PC, F2 -IsoP, and TBARS in all participants were investigated using stepwise multiple regression analysis. In PC, age (β = − 0.11, P = 0.002 ), leg extension power (β = − 0.12, P = 0.008 ), BMI (β = 0.12, P = 0.004 ), and HDL-C (β = 0.08, P = 0.040 ) were included in the regression model (adjusted R 2 = 0.018 ). In the F2 -IsoP, smoking status (β = 0.07, P = 0.060 ), BMI (β = 0.07, P = 0.054 ), and HbA1c (β = − 0.06, P = 0.089 ) were included in the regression model (adjusted R 2 = 0.006 ). In TBARS, glucose (β = 0.18, P < 0.001 ), CRF (β = 0.16, P < 0.001 ), age (β = 0.15, P < 0.001 ), TG (β = 0.11, P = 0.001 ), antioxidant supplementation (β = 0.10, P = 0.002 ), and HbA1c (β = − 0.13, P = 0.004 ) were included in the regression model (adjusted R 2 = 0.071 ). In conclusion, the present study showed that age, anthropometric index, lifestyle-related parameters, medication and supplementation status, objectively measured physical fitness, biochemical parameters, and nutritional intake status explain less than 10% of oxidative stress at rest.